COMPARATIVE STRENGTH CALCULATION CONTACT SHPONKOVOHO SEAM ACCORDING TO THE STANDARD AND VARIATIONAL METHOD BASED ON THE THEORY OF PLASTICITY CONCRETE - and; and (Municipal economy of cities. Series: «Economy science», 2013)
The comparative analysis of results of calculation of durability of contact seam is executed after different existent methods.